Shear margins in upper half of Northeast Greenland Ice Stream were established two millennia ago - Daniela Jansen; Steven Franke; Catherine C. Bauer; Tobias Binder; Dorthe Dahl-Jensen; Jan Eichler; Olaf Eisen; Yuanbang Hu; Johanna Kerch; Maria-Gema Llorens; Heinrich Miller; Niklas Neckel; et al. (Nature Communications, 2024)
Abstract Only a few localised ice streams drain most of the ice from the Greenland Ice Sheet. Thus, understanding ice stream behaviour and its temporal variability is crucially important to predict future sea-level change. The interior trunk of the 700 km-long North-East Greenland Ice Stream (NEGIS) is remarkable due to the lack of any clear bedrock channel to explain its presence. Here, we present a 3-dimensional analysis of the folding and advection of its stratigraphic horizons, which shows that the localised flow and shear margins in the upper NEGIS were fully developed only ca 2000 years ago. Our results contradict the assumption that the ice stream has been stable throughout the Holocene in its current form and show that upper NEGIS-type development of ice streaming, with distinct shear margins and no bed topography relationship, can be established on time scales of hundreds of years, which is a major challenge for realistic mass-balance and sea-level rise projections.